2015
DOI: 10.1515/pophzn-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Son Preference, Parity Progression and Contraceptive Use in South Asia

Abstract: Background: The desire for sons has long been recognised as a significant determinant of childbearing decisions throughout most of South Asia. This paper provides an overview of the stated desire for sons and the manifestations of son-preferring behaviour in relation to parity progression and contraceptive use. Methods: This paper uses the most recently available Demographic and Health Survey (or equivalent) data from five South Asian countries: Afghanistan, Bangladesh, India, Nepal and Pakistan. The extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Men with three or more sons only were more likely to use sterilization methods than couples having less than two sons and at least one daughter. These findings also confirm that son preference is stronger in Nepal than Bangladesh as has been reported previously [18, 19]. Furthermore, the researchers showed an association between use of traditional methods and sex composition of children.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Men with three or more sons only were more likely to use sterilization methods than couples having less than two sons and at least one daughter. These findings also confirm that son preference is stronger in Nepal than Bangladesh as has been reported previously [18, 19]. Furthermore, the researchers showed an association between use of traditional methods and sex composition of children.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown stronger association of son preference with contraceptive use pattern in Nepal compared to other South Asian countries [18, 19]. Furthermore, strong son preference was expressed through increased proportion of permanent method users after two or three sons compared to those having no son [19]. In addition, Leone et al showed that son preference was expressed through differential stopping of child bearing [6].…”
Section: Introductionmentioning
confidence: 99%
“…Stalling contraceptive prevalence rates and the consequent slowdown of fertility decline may indicate that women are having additional children in the pursuit of sons. Previous studies have also found that the number of living sons is associated with intentions to have additional children, intentions to use contraception, and subsequent fertility (Mahmood and Ringheim 1996; Sathar and Casterline 1998; Casterline, Sathar, Haque 2001; Hussain, Fikree, and Berendes 2000; Muhammad 2009; Channon 2015). …”
Section: The Pakistani Experiencementioning
confidence: 93%
“…Women with fewer than two children are, by and large, considerably less to avail themselves of permanent contraception. On the other hand, the preference for sons has no real relationship with the choice in traditional and temporary contraceptive methods in this region ( Channon, 2015 ). In addition, women in rural areas with high infant mortality rates are less likely to use contraceptives than women in urban areas with low infant mortality rates ( Thang et al., 1992 ).…”
Section: Introductionmentioning
confidence: 99%